Implementasi Nilai-nilai Pancasila dalam Pembentukan Sistem Hukum Nasional - Kurdi; Arbani, Muhammad (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to examine the implementation of Pancasila values ​​in the formation of Indonesia's national legal system, by highlighting the challenges and obstacles faced, as well as offering strategic solutions to overcome them. As a basic state norm (staatsfundamentalnorm), Pancasila has a central role in the national legal system to create laws that reflect the character, justice and identity of the Indonesian nation. However, the process of integrating Pancasila values ​​is faced with various obstacles, such as incompatibility with customary legal norms, weak law enforcement, and social dynamics due to globalization. This research uses normative juridical methods with statutory and conceptual approaches to analyze the relevance of Pancasila values ​​in various legal products. The research results show the importance of legal reform, cross-sector dialogue, improving legal education, and community involvement in the legislative process. With this holistic approach, it is hoped that the integration of Pancasila values ​​can create a national legal system that is fair, inclusive and relevant to current developments without losing its philosophical roots.